Persepsi Anak tentang Storytelling sebagai Media Pengembangan Budaya Literasi - Putu Santi Oktarina; Komang Trisnadewi; Ni Luh Gede Dita Indah Sari (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims at describing children’s perception towards the development of early childhood literacy culture through storytelling activities. It is an effort to support government programs in the success of the school literacy movement to increase reading interest and reading culture in students. The rapid development of the flow of information requires the public to be wise in filtering information which is also part of the principle of literacy development. Therefore, the Department of English Education chooses storytelling to improve and motivate children to develop their reading interests as an early reflection of the formation of a literacy culture. It was given eight times. After that the team surveyed to find out the child's perception of their interest and understanding. The results showed positive responses from students with an average percentage above 98%. This response, of course, requires a follow-up, namely habituation of the school literacy movement.